Faith at the interface of cultures: law and gospel, Johannine communities, and Hebrews - Broadhead, Edwin K.; Foster, Paul; Kraus, Wolfgang (Biblische Zeitschrift, 2024)
Front Cover -- Contents -- Preface -- Chapter 1. From Fundamentalism to Fundamentals -- Part One Faith and Culture: The Interface of Law and Gospel -- Chapter 2. Divorce in the New Testament in Light of Jewish Tradition -- Chapter 3. The Beatitudes in Matt 5.3-12 and the Matthean Understanding of Torah Practice -- Chapter 4. Law and Culture in 1 Corinthians 7: The Status of the Children -- Chapter 5. Did Abraham's Childlessness and Sterility Imply His Ungodliness? Sexuality and Justification by Faith in Romans 4 -- Chapter 6. Law and Wisdom in the Letter of James -- Chapter 7. Christology and Praxis: A Reading of Matthew 11:2-16:23 -- Chapter 8. The Love Commandment and its Transcendence in the Gospel -- Part Two Faith and Culture in the Context of the Johannine Communities -- Chapter 9. Replacement or Superstructure? Law and Gospel in the Fourth Gospel -- Chapter 10. John's Appeal to a Gentile Audience -- Chapter 11. The Role and Status of the Law in the Fourth Gospel -- Chapter 12. „Sokrates aber lächelte …" (Platon: Phaid 15) Jesu Begräbnis nach Johannes (19,38-42) im Licht platonischer Anthropologie -- Chapter 13. The Reception of the Gospel of John in the Gospel of Nicodemus/Acts of Pilate (rec. Greek A) -- Chapter 14. Heraclitus and the Journey of the Johannine Community -- Chapter 15. Jesus as Life-giver in the Gospel of John -- Part Three Faith and Culture in the Context of the Letter to the Hebrews -- Chapter 16. The Ancient Transmission of the Epistle to the Hebrews -- Chapter 17. Zur Rezeption von Psalm 8 im Hebräerbrief -- Chapter 18. He Had to Become Like His Brothers and Sisters: Redefining the Priesthood in Hebrews -- Chapter 19. High Priesthood Christology and Atonement in Hebrews: A Conversation with Bill Loader -- Chapter 20. The Use of Melchizedek Tradition and the Fluidity of "Sacred Margins" in the Letter to the Hebrews.